Analisis Logam Besi (Fe) Dalam Air PDAM Di Kabupaten Pidie Jaya Menggunakan Spektrofotometer Serapan Atom - Ernita Silviana; Indah Fajarwati; Yuni Dewi Safrida; Elfariyanti Elfariyanti; Rinaldi Rinaldi (Fakultas Teknik, 2020)
All living things need water, because water is the most important essential material for life. One of the substances in water is iron (Fe). According to Permenkes RI number 492 / MENKES / PER / VI / 2010 levels of iron (Fe) allowed in drinking water is 0.3 mg/L. This study aimed to determine the amount of Fe metal content in PDAM water in Pidie Jaya Regency (Mon Krueng Meureudu PDAM, Panteraja PDAM, and Ulim PDAM) using the Atomic Absorption Spectrophotometry (SSA) method with wet destruction. The results of the analysis of iron content in PDAM water in Pidie Jaya Regency are PDAM Ulim 0.0628 µg/L, Panteraja PDAM 0.1068 µg/L, and Meureudu PDAM 0.0055 µg/L. In other words, PDAM water in Pidie Jaya Regency is still at the specified level. It is expected that PDAM Pidie Jaya will continue to maintain the quality of iron (Fe) levels so as not to exceed the maximum levels that have been set.